Left anterior descending artery dissection with retrograde aortic dissection during percutaneous coronary intervention: a case report - Ahn, Seha; Lee, Heejin; Choi, Jung Suk; Moon, Youngkyu; Kim, In-Sub; Choi, Si Young; Kang, Joon Kyu (Frontiers in Surgery, 2023)
Retrograde catheter-induced coronary artery dissection during percutaneous coronary intervention is an exceedingly rare occurrence, and the likelihood of it extending into the aorta is even more uncommon. Typically, surgical treatment involves aortic root replacement combined with coronary artery bypass grafting. However, in this particular case, a meticulous approach was employed. By carefully guiding wires into the true lumens and placing stents in the proximal left main and left anterior descending arteries, the immediate complications were averted by obstructing the retrograde flow in the false lumen. Subsequently, an off-pump coronary artery bypass was performed using the left internal mammary artery to the left anterior descending artery, without the need to manipulate the aorta. This approach resulted in a short operation time and the absence of any other complications.